Interpretation of the borderline space on the example of neighbouring towns of central Slovakia: Banska Bystrica and Zvolen - Koštialová, Katarína; Darulová, Jolana (Studia Etnologiczne i Antropologiczne, 2013)
The aim of considerations is the analysis of the cultural space of neighbouring places situated in central Slovakia, namely Banska Bystrica and Zvolen. Basing on historical and ethnographic data the attempt was made to show the existence of various types of borders between the centers in question (a geographic, political, economic, economic, cultural and linguistic one). The emptirical studies assumed that the way of perceiving and interpreting the influence of the the very borders on people’s daily life, as well as their former and current influence on the local / town identity of inhabitants will be captured. The emphasis was put on presenting the actions of the inhabitants having a competitive and cooperative nature that have shaped the present-day economic, social and cultural needs, as well as the influence of a domestic and local politics aiming at forming one regional centre.